EFEKTIVITAS PELAKSANANA KURSUS MENJAHIT DI SANGGAR KEGIATAN BELAJAR KABUPATEN ENREKANG - Yunus Busa; Suparman Suparman (JURNAL EDUKASI NONFORMAL, 2019)
Non-formal education has its own advantages in its role which contributes to overcoming unemployment and poverty alleviation through courses or life skills education. The purpose of this study was to determine how the effectiveness of the implementation of the sewing course at the Enrekang Learning Activities Studio in the input, process and output.The approach used in this study is a qualitative approach, namely by viewing the object of study as a system, meaning that the object of study is seen as a unit consisting of interrelated elements and describing the phenomena that exist with a population of 20 and the research sample is the whole of the population .The results showed that the effectiveness of the sewing course implementation in the Enrekang learning center in terms of input can be said to be effective. The effectiveness is seen in terms of the instructor has met the requirements and the instructor has conducted training in accordance with the steps in the implementation of learning, in terms of students, in terms of curriculum or teaching material, in terms of facilities and targets of learning activities is very adequate, as well as the evaluation and supervision aspects carried out by the manager of the Enrekang District Learning Activities Studio, the effectiveness of the sewing course implementation in the Enrekang district learning activities center in terms of the process can be said to be effective